2018
DOI: 10.1093/jamia/ocy064
|View full text |Cite
|
Sign up to set email alerts
|

The National Sleep Research Resource: towards a sleep data commons

Abstract: ObjectiveThe gold standard for diagnosing sleep disorders is polysomnography, which generates extensive data about biophysical changes occurring during sleep. We developed the National Sleep Research Resource (NSRR), a comprehensive system for sharing sleep data. The NSRR embodies elements of a data commons aimed at accelerating research to address critical questions about the impact of sleep disorders on important health outcomes.ApproachWe used a metadata-guided approach, with a set of common sleep-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
336
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 525 publications
(365 citation statements)
references
References 28 publications
2
336
0
1
Order By: Relevance
“…Many authors concluded their paper suggesting that having access to more data would most likely improve the performance of their models. With large datasets becoming public, such as the TUH Dataset [65] and the National Sleep Research Resource [217], deeper architectures similar to the ones used in computer vision might become increasingly usable. However, it is important to note that the availability of data is quite different across domains.…”
Section: Datamentioning
confidence: 99%
“…Many authors concluded their paper suggesting that having access to more data would most likely improve the performance of their models. With large datasets becoming public, such as the TUH Dataset [65] and the National Sleep Research Resource [217], deeper architectures similar to the ones used in computer vision might become increasingly usable. However, it is important to note that the availability of data is quite different across domains.…”
Section: Datamentioning
confidence: 99%
“…We conducted a longitudinal retrospective study using data collected from the Sleep Heart Health Study (SHHS) [10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…Participant data was accessed from the Cleveland Family Study (CFS) via the National Sleep Research Repository. [36][37][38][39] The CFS was conducted as a longitudinal study of sleep apnea and included 2284 individuals from 384 families over 16 years of follow up. All data were collected with written informed consent under protocols approved by a local institutional review board at each institution.…”
Section: Participantsmentioning
confidence: 99%
“…Given that slow wave activity is described to have different functions between stage N2 and stage N3 sleep, 45 we sought to characterize populations of slow waves from each sleep stage independently using surface EEG overnight recordings from subjects within the Cleveland Family Study. [36][37][38][39] Notably, the distinction between sleep stages is imperfect, and most often a mixing of lighter and deeper sleep occurs, particularly in transitions between sleep stages. 46,47 Further, individual variability of slow waves and spindles has been demonstrated with regard to frequency and timing aspects of coupling.…”
Section: Stage N2 and Stage N3 Slow Waves Demonstrate Distinct Composmentioning
confidence: 99%
See 1 more Smart Citation